Implication of primary decoding in the third grader's reading comprehension process - Ayala Castillo, Maria Liliana; Sarmiento Álvarez, Fady Luzmila; Guerrero Barón, Aislen Vanesa (Rastros Rostros, 2002)
Reading is "the key to the main door of knowledge" this is the privileged tool of intelligence since the act of reading allows the entry of new concepts and new knowledge to the human brain which enriches and develops the interpretative capacity of the individual.